The Hyperreality of Fiction Idol on K-Pop Demon Hunters Animation through The Fandom's Fast-Paced Transmedia Storytelling - Arif Zuhdi Winarto (Universitas Negeri Yogyakarta, 2026)
This study examines how K-Pop Demon Hunters became a transmedia phenomenon through the rapid circulation of fan and creator responses across digital platforms. Using netnography, it analyzes six YouTube Shorts videos that circulated around the film shortly after its Netflix release, including parody, AI-generated realism, official choreography, behind-the-scenes content, cosplay, and vocal performance. The study finds that the film’s fictional idol groups were repeatedly re-staged as if they were real K-pop acts through a combination of participatory fan practices, studio-produced content, and independent creator labor. Drawing on Jenkins’s participatory culture and transmedia storytelling, Baudrillard’s hyperreality, and Virilio’s dromology, the analysis shows how speed, repetition, and visual realism helped blur the boundary between fiction and reality. Rather than functioning only as an animated film, K-Pop Demon Hunters evolved into a distributed media event in which audiences actively expanded the narrative across platforms. The study contributes to media and fandom studies by showing how fictional idols can gain cultural legitimacy through transmedia circulation, platform-based participation, and collective audience imagination.